Ossifying Fibroma of Maxilla in a Female Affected by Neurofibromatosis Type 1 - Jendi, Shoeb Kasim (Indian J Otolaryngol Head Neck Surg, 2018)
Ossifying fibroma is a benign fibro-osseous lesion found exclusively in jaws. It has a predilection for premolar–molar region in the mandible. The occurrence of OF as solitary lesions with no underlying disease is common in jaws. However its co-existence in patients with neurofibromatosis type 1 (NF1) has not been described in jaws. NF1, also known as von Recklinghausen’s disease or peripheral neurofibromatosis, is an autosomal dominant multisystem disorder that approximately affects 1 in 2500–3000 births. The common manifestations of this disease include Café-au-lait macules, skinfold freckling, cutaneous neurofibromas, blue-red and pseudoatrophic macules on skin, plexiform neurofibroma, scoliosis, optic glioma. So far only one case of ossifying fibroma (OF) in such patients has been reported in the skull but not in the maxillofacial region. We report a case of OF of the maxilla in a 45 year old female suffering from NF1. To the best of our knowledge this is the first case report where OF occurred in the maxilla in patient with NF1.